Poly-γ-glutamic acid-producing bacteria reduce wheat Cd uptake by promoting Cd transfer from macro-to micro-aggregates in Cd-contaminated soil - Wang, Xiaohan; Liu, Xiaoyu; Ji, Haikuan; Xia, Tao (Frontiers in Environmental Science, 2023)
Heavy metal immobilization using poly-γ-glutamic acid-producing bacteria is a novel and environmental friendly technique for the remediation of heavy metal-contaminated soil. However, only few studies have investigated the effects of γ-PGA-producing bacteria on the Cd uptake of wheat plants and the Cd distribution in soil aggregates in Cd-polluted soils. In this project, the Cd immobilization effect and mechanism of the γ-PGA-producing bacteria Bacillus subtilis W7 and Bacillus amyloliquefaciens W25 were investigated based on solution culture and pot experiments. In these two bacteria-inoculated culture media, the concentration of Cd decreased, whereas the pH, cell growth, γ-PGA production and cell-immobilized Cd significantly increased over time. Strain W25 exhibited a higher ability to produce γ-PGA and immobilize Cd than strain W7. In the pot experiments, the grain Cd content of wheat was reduced by 24–35% and the DTPA-Cd content was decreased by 22–37% in the rhizosphere soils with inoculation of both strains compared to the control. Furthermore, strain W25 had a greater ability to decrease the grain Cd uptake than strain W7. Inoculation with the two strains significantly increased the pH, organic matter content, and ur ease activity, and promoted the migration of Cd from large fractions (> 0.25 mm) to small fractions (< 0.048 mm) and the transformation of available Cd to unavailable Cd in wheat rhizosphere soil. Our results highlight the potential of γ-PGA-producing bacteria in remediating Cd-polluted soils and safely producing wheat.